Infantile hepatic hemangioendothelioma associated with pulmonary arterial hypertension and cardiac insufficiency successfully treated with oral propranolol-a rare case report - Debashree Priyadarshini; Goolla Akhila; Rachita Sarangi; Anuspandana Mahapatra (SpringerOpen, 2023)
Abstract Background Infantile hepatic hemangioendothelioma (IHHE) is a benign liver tumor associated with a varied spectrum of presentations ranging from asymptomatic hepatomegaly and cutaneous hemangiomas to some life-threatening complications like cardiac failure, consumptive hypothyroidism, pulmonary arterial hypertension, gastrointestinal bleeding, and coagulopathy. Hypothyroidism results from increased activity of type 3 iodothyronine deiodinase in the liver. Clinico-radiological correlation is essential for a definite diagnosis. Although children with asymptomatic lesions may experience spontaneous regression within a year, those with symptomatic lesions require aggressive management due to the risk of mortality once the symptoms commence. Treatment modalities can be either pharmacologic or interventional depending on the clinical presentation, with propranolol being considered the first-line agent. Case presentation Here, we describe a 2-month-old female infant with progressive abdominal distension, signs of congestive cardiac failure, and pulmonary arterial hypertension, confirmed as IHHE by abdominal ultrasonography and contrast-enhanced MRI. It was complicated by consumptive hypothyroidism and coagulopathy. The child was successfully treated with oral propranolol, levothyroxine, and supportive measures. Conclusion Early aggressive treatment in a symptomatic patient is linked to successful outcomes. Hypothyroidism should be focused on and managed earlier to prevent intellectual and growth retardation.